Temperatura ambiente e concentrações séricas de cortisol em suínos em crescimento-terminação - Fagundes, Antonio César Alves; Negrão, João Alberto; da Silva, Roberto Gomes [UNESP]; Gomes, Jacinta Diva Ferrugem; Souza, Luiz Waldemar de Oliveira; Fukushima, Romualdo Shigueo (My University, 2008)
Thirty-six castrated males and females Landrace x Large-White pigs (74 to 149 days of age) were randomly allotted to two environmental conditions: high temperature in a climatic chamber (HT; 22.2 to 32.8 °C) and comfort temperature in a conventional shed (CT; 17.6 to 26.6 °C), with night-and-day variations. Blood samples were weekly collected from animals of both HT and CT conditions for determination of serum cortisol levels. Cortisol levels of both sexes were not different, and there was no interaction with environmental temperature. Pigs of HT showed significantly higher average cortisol level (P<0.01) than the CT ones (7.06 and 4.82 mg/dL, respectively). Increasing in serum cortisol was continuous and linear (P<0.05) during the experimental period, suggesting the cortisol as a possible indicator of the heat stress in growing-finishing pigs.
Environmental temperature and serum cortisol levels in growing-finishing pigs
Keywords: Concentration; Cortisol; Heat stress; Swine; Animalia; Pieris brassicae; Suidae